Confirmation of the presence of Scyliorhinus retifer (Garman, 1881) in the southwestern Gulf of Mexico - Del Moral-Flores, Luis Fernando (2018)
The chain catshark, Scyliorhinus retifer, is an oviparous demersal species from the northwestern Atlantic. The southern limit of distribution of this species is not clearly established. In the Gulf of Mexico, most of its records correspond to the northeastern area and are sporadic. The presence of the species and its morphometry is reported here based on two mature male specimens, 518 and 527 mm in total length, captured on the southwestern coast of the Gulf of Mexico.